Oncogene-induced autophagy and the Goldilocks principle - MARTIN, SEAMUS (My University, 2011)
Although several oncogenes enhance autophagic flux, the molecular mechanism and consequences of onco - gene-induced autophagy remain to be clarified. We have recently shown that expression of oncogenic H-Ras V12 pro - motes autophagy through upregulation of Beclin 1 and the BH3-only protein Noxa. H-Ras-expressing cells undergo autophagic cell death as a result of Noxa- mediated displacement of Mcl-1 and Bcl-x L from Beclin 1. Oncogenic H-Ras- induced death is attenuated through knockdown of BECLIN 1 , ATG5 or ATG7 , or through overexpression of Mcl-1, Bcl-2, Bcl-x L and their close rela - tives. T
PUBLISHED
Keywords: autophagic flux; autophagic flux